Analisis Lagu Anak-anak Ciptaan A.T. Mahmud - Aditya Krismay Naky; Jagar Lumbantoruan (SENDRATASIK UNP, 2021)
The purpose of this study was to analyze and describe children's songs created by AT Mahmud. This type of research is content analysis research. The main instrument in this study was the researcher himself and assisted with a set of musical instruments such as guitars. Data collection techniques are carried out by means of observation, documentation and library studies. The steps of analyzing data are collecting data, clarifying data, describing data and concluding data. Based on the results of the analysis of three children's songs by A. T. Mahmud shows that the musical characteristics of the song A. T. Mahmud are; 1) processing dominant rhythmic motifs undergo reps; 2) more melodic movements using stepping movements (M2 and m2 intervals); 3) Dominant melodic motif processing techniques using sequence techniques; 4) Chord progressions only use the main chords I, IV and V (major / minor); 5) the dominant cadens appear namely Authentic cadense; 6) the birama marks used are 2/4, 3/4, and 4/4; and 7) Cemara, Kereta Keretaku and Pemandangan songs fall into the category of one- and two-part form songs. Based on the musical characteristics of the song created by A. T. Mahmud caused the songs to remain sung and survive to this day. The element of simplicity in the selection of tone, rhythm, and harmony remains A.T Mahmud's consideration in making children's songs so that they are easy to sing and beautiful to hear.